Developing Ways of Thinking in Society Using Online Video: A Case of Sexy Killers Video - Limano, Ferric (Humaniora, 2019)
This research aimed to explain the online video, ?Sexy Killers?, to build a way of thinking in society. The problem of this research limited to the role of online video in conveying messages that could build positivity in the community. It had a focus on how much the impact of online video could affect the way of thinking in society by using online video ?Sexy Killers? and looked at the responses of the audience?s comments after receiving the message contained in this video. The method used in the research was a qualitative method documentation that the researcher would document any opinion in column comments by giving the right impression that had obtained positive (build) and negative. The results of this research are the video ?Sexy Killers? has succeeded in design online video recommendations that can build a way of thinking in a society that has a positive impact.